Currently Available Biomarkers and Strategies for the Validation of Novel Candidates for Neurochemical Dementia Diagnostics in Alzheimer's Disease and Mild Cognitive Impairment. (18th June 2014) - Lewczuk, Piotr
Abstract : The number of people afflicted with Alzheimer's disease (AD) and other types of dementing conditions has grown exponentially in the last decades. This review focuses on the diagnostic role of the classic cerebrospinal fluid (CSF) biomarkers of neurochemical dementia diagnostics (NDD) and critically discusses potential strategies for the development and validation of novel potential candidates. In some countries, NDD is already established as a routine diagnostic tool, used for the evaluation of patients with cognitive impairments. On the other hand, preanalytical and technical issues, partly discussed in this paper, prevent NDD from the general acceptance worldwide. Currently, two groups of biomarkers in the CSF are considered in NDD: amyloid β (A β ) peptides and Tau proteins, including the hyperphosphorylated forms of the latter (pTau). The analyses of these two groups of biomarkers can reveal pathologic alterations as early as twenty years before the onset of clinical symptoms. In mild cognitive impairment (MCI), NDD can reliably predict which individuals are at risk of converting to AD. The roles of biomarkers of amyloid β deposition in the brain tissue (including the CSF concentration of A β 42) and biomarkers of neurodegeneration (including the CSF concentrations of Tau/pTau proteins) are reflected in the currently proposed diagnostic criteria for AD and MCI.